Lithium Extraction Methodology and Recovery from Conventional Resources: A Critical Review - Himyan Mohammed Akbar (22928320) (2025)
Lithium recovery from various primary sources, such as brine, ores, seawater, and clay, or secondary resources that include lithium-ion batteries (LIB) and lithium-ion metal oxide batteries (LIMOB) poses a challenge due to the complexity of the extraction processes. This review aims to examine recent advancements in lithium extraction and recovery from both primary and secondary sources. It provides an overview of the established recovery and separation techniques for primary sources, including precipitation, chromatography, ion exchange, and membrane technologies, alongside the chemical agents used in these processes. Additionally, lithium recovery from secondary sources through methods such as hydrometallurgy, pyrometallurgy, and bioleaching, highlighting the use of various organic and inorganic sorbents, is also addressed. Some of the advantages and disadvantages of the recovery techniques, as well as economic, environmental, and technical data analysis, are also discussed. While the recovery of lithium from primary sources has been extensively studied, secondary sources—particularly spent LIBs and LIMOBs—have received relatively less attention, mainly due to challenges such as the hazardous nature of recycling processes, stringent environmental regulations, high operational costs, and significant energy requirements. Nevertheless, the emergence of bioleaching technologies offers a promising alternative technique for lithium recovery from secondary sources, owing to their potential for environmentally sustainable operations, cost-effectiveness, and lower energy consumption, availability of materials and bio-organisms, despite the new emergence for lithium recovery from secondary resources. The major highlight of this review paper is the comparison of each recovery technique. Among the primary resources -brine, ore, clay- recovery techniques, precipitation techniques were found to recover ~ 99.5% of lithium in the form of lithium chloride (LiCL), while membrane and chromatography managed to recover ~ 98%, and lastly, 78% using liquid–liquid extraction techniques. However, by implementing the hydrometallurgy technique to recover lithium from secondary resources in the form of lithium fluoride (LiF), lithium phosphate (Li3PO4, and lithium carbonate (Li2CO3), only ~ 88% of lithium salts were recovered, while in pyrometallurgy similar recovery percentage was noticed, 87%. Additionally, a 70 ~ 96% recovery rate is reached using bioleaching and microorganisms. Other Information Published in: Water, Air, & Soil Pollution License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11270-025-08382-4